Analisis Persepsi Wakif Terhadap Wakaf Tunai di BWI Sumatera Utara - Imsar; Franaya Al Arfa; Khairina Tambunan (Badan Wakaf Indonesia, 2021)
The purpose of this study was to determine the perception of wakif on cash waqf at BWI North Sumatra. This study uses a descriptive qualitative method, by taking the object of research at BWI North Sumatra. As the research informant, Nazhir from BWI North Sumatra, the wakif. This study explains that there are 5 indicators used to measure the perception of wakif, namely internal indicators consisting of income and understanding, and external indicators, namely information media, convenience and benefits of cash waqf at BWI North Sumatra. Based on the results of the data questionnaire assessment, that 73.3% of wakif stated that it was good from the income indicator. This means that wakifs have a good perception of cash waqf that the more prosperous the community, the greater the potential for cash waqf. From the indicators of understanding, 46.7% of wakifs said they were good with cash waqf. That is, wakif has a good perception of cash waqf in terms of understanding so that awareness arises in advancing the Islamic economy through cash waqf. From the information media indicators, 43.3% of wakif stated that they were neutral towards the perception of wakif in terms of access to information media. This means that BWI SU should further promote information media through online media in the digital era. From the convenience indicator 46.7% wakif answered well. This means that wakifs have a good perception of the convenience provided in accessing BWI SU for cash waqf collection transactions for wakifs. From the benefits indicator 56.7% wakif answered well. This means that wakifs have a good perception of the benefits of cash waqf, which can train the social spirit and help people in need. Keywords: Perception, Cash Waqh, BWI Sumatera Utara